The calculation of fluid flow through a torque converter turbine at stall - Van der Merwe, Joachim Christoffel (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2005.